Tinjauan Penerapan Analisa Jabatan dan Komunikasi Organisasi sebagai Pengukuran Motivasi dan Dampaknya pada Kinerja Karyawan Berdasarkan Pendekatan SPSS VS LISREL - Kristanto, Antonius Nico; Sarjono, Haryadi (Binus Business Review, 2012)
PT Indo Nuansa Jaya is a chemical materials manufacturing company for oil drilling and drilling tools in Indonesia. The selling level of chemical materials for drilling in 2008 has reached to 348 units, in 2009 to 549 units, and in 2010 decreased to 447 units. The research method used is survey method; meanwhile the research type is associative. Data is gathered from questionnaire to employees. Data processing is using SPSS 16.0 and then compared to the result from data processing using LISREL 8.80. The research resulted that the analysis of duties has relation in 0,628 and has significant influence in (0.516)2 = 26.63% towards motivation. From the result, it could be founded that motivation could influence employees performance in (0.412)2 or 16,97%.